Homologous homoclinic solutions based on DPI traffic asymmetry - Jie PAN; Feng GAO; Dong LIU; Zhao DONG; Huifang HOU (Dianxin kexue, 2016)
In the field of current internet application analysis, in order to obtain more accurate basic data, traffic collection needs to ensure the integrity of each session traffic. The cause of traffic asymmetry and the impact analysis, combined with the actual needs of business analysis, homologous homoclinic flow merge the basic ideas and solutions were proposed.